Perancangan Sistem Pemantauan Kualitas Air Berbasis IoT pada Kolam Ikan Hias Air Tawar - Shania Bakhtiar Paturusi; Andi Susilo (Journal TIFDA (Technology Information and Data Analytic), 2025)
This study focuses on designing an IoT-enabled monitoring system to enhance water quality management in freshwater ornamental fish ponds, with an emphasis on tracking temperature, pH, and total dissolved solids (TDS). Utilizing an ESP32 microcontroller along with DS18B20, pH, and TDS sensors, the system collects and transmits real-time water quality data via the Blynk platform. The findings demonstrate that the system effectively monitors temperature, pH, and TDS levels, initiating corrective actions like activating a water heater or solenoid valve when needed. By automating these processes, the system minimizes the need for manual checks, improves resource efficiency, and supports optimal guppy fish farming conditions.